А. П. Сапунов: историко-этнографические исследования территории белорусских земель в произведениях конца XIX в. - Функ, Ю. В. (Мінск : БДУ, 2013)
Article is devoted to historical and ethnographic researches of the known historian and the researcher of Vitebsk edge Alexey Parfenovich Sapunov (1851–1924). A. P. Sapunov was born near Velizha in the item of Usvyata and in a consequence I became honourable citizen Velizha. Having graduated from historical and philological faculty of the St. Petersburg university, A. P. Sapunov all the life I devoted to studying of history and culture of the people occupying the Vitebsk province along Zapadnaya Dvina. In article questions of ethnography and study of local lore of Belarus and Russia by A. P. Sapunova’s estimates from a position of the XIX century on examples of Polotsk, as historical center are considered. A. P. Sapunov was the representative of the West Russian direction. It was close on views and belief to the Russian Slavophiles, and, as well as they, was the convinced supporter of preservation and development of the Belarusian originality. At this A. P. Sapunov firmly I stood on a position of all-East Slavic and all-Russian unity. = Посвящена историко-этнографическим изысканиям известного историка и исследователя Витебского края Алексея Парфеновича Сапунова (1851–1924). Уроженец п. Усвяты, что недалеко от Велижа, впоследствии стал почетным гражданином этого города. Окончив историко-филологический факультет Санкт-Петербургского университета, А. П. Сапунов всю свою жизнь посвятил изучению истории и культуры народов, населявших Витебскую губернию вдоль Западной Двины. Рассматриваются вопросы этнографии и краеведения Беларуси и России по оценкам А. П. Сапунова с позиции XIX в. на примерах г. Полоцка как исторического центра. А. П. Сапунов являлся представителем западнорусского направления.